Islamic Law and Positive Law Protection for Victims of False Accusations of Adultery in the Modern Era - Aicha Azdina Adly Fesya; M. Fazli Pratama; Rayhan Nandini Telaumbanua; Siti Salmiah Dalimunthe; Habiburriziq El Ardhy Saragih (ISNU Sumatera Utara, 2026)
This study employs a normative qualitative method with an analysis of classical and contemporary literature. The paper examines accusations of zina and legal protection for victims in the digital era. The background of the study is rooted in the complexity of the dissemination of zina allegations through social media and digital communication platforms, which have serious implications for individual honor, social reputation, and moral integrity. From the perspective of Islamic jurisprudence, unsubstantiated allegations are categorized as qadhf, requiring stringent evidentiary standards, including the testimony of four morally upright male witnesses or a voluntary confession, with violations attracting multidimensional sanctions such as corporal punishment, social discredit, and spiritual accountability. Indonesian positive law provides protection through the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), allowing victims to pursue criminal liability, compensation, and reputational rehabilitation. The results indicate that effective legal protection requires a multi-layered approach integrating law enforcement, technological interventions, and public education to restore victims’ social credibility and enhance deterrence against false accusations.